THE RELATIONSHIP OF MULTIMEDIA, THE INTERNET TO THE DEVELOPMENT OF LEARNING FOR THE MILLENIAL GENERATION - Lilis Suryani,; Arman Syah Putra,; Nurul Aisyah, (Journal of Innovation Research and Knowledge, 2022)
The background of this research is how to find out what variables can affect the development of learning for the current millennial generation, especially during the current pandemic. The variables raised in this study are multimedia variables and internet variables. The method used in this study is to use quantitative methods by conducting a survey to 100 parents of students who will generate data and process it using SPSS media so that it can produce answers to the formulation of the problems raised in this study. The problem raised in this study is how to find out the variables that can affect the development of learning, especially for the millennial generation who are very sensitive to changing times multimedia and internet variables. The purpose of this study is how to find out how multimedia variables and internet variables can affect educational development variables with very significant results, namely 0.003 on multimedia variables and educational developments and also produce a value of 0.002 on internet variables and educational development only produce significant cells, then these variables can affect variables with education